Failure to reduce the risk of postoperative lower genital tract infection with perioperative antibiotic prophylaxis during induced abortion: a real-world study - Ding, Jing; Zhang, Yan; Gu, XiangYing; Che, Yan (Frontiers in Medicine, 2024)
Objective: This study aimed to evaluate perioperative antibiotic use for induced abortion and its association with lower genital tract infections (LGTI) two weeks post-surgery in China. Methods: We conducted a prospective cohort study of women seeking induced abortion. We interviewed participants on the day of surgery and two weeks after, and evaluated preoperative tests, gynecological exams, perioperative antibiotic usage, postoperative vaginal microbiota, and LGTI diagnosis. Multivariate logistic regression was used to assess the association between the perioperative antibiotic use and LGTI risk. Results: We recruited 8,190 women undergoing induced abortion at 27 participating hospitals. Of these, 95% had gynecological exams, but over 80% lacked tests for vaginal microbiota, chlamydia, and gonorrhea. Approximately 20% of those examined had increased vaginal discharge and abnormal vaginal cleanliness. The positive rates for gram-positive rods, fungi, and trichomonas were 38.6%, 2.4%, and 0.3% respectively. More than three-quarters (78.5%) of participants received antibiotics, mainly second-gen cephalosporins (36.8%) and nitroimidazoles (12.3%). LGTI rates two weeks post-surgery were 2.7% for antibiotic recipients and 3.1% for non-recipients, with no statistically significant difference (P>0.05). Logistic regression showed no association between perioperative antibiotic use and LGTI risk (OR=1.01, 95% CI 0.59-1.74). However, this risk increased with abnormal preoperative discharge tests (OR=1.39, 95% CI 1.04-1.86). Conclusion: Most Chinese women undergoing induced abortion used perioperative antibiotics, but this didn't significantly reduce LGTI risk. Instead, this risk was related to abnormal preoperative discharge tests. Standardization of perioperative antibiotic use for induced abortion is recommended, and prophylactic treatment in Chinese abortion services warrants further investigation.